Studying for finals I have come across a result that I understand how the system is derived but I cannot solve the system. I feel like this should be trivial, but I do not know where to go. Through Gaussian Quadrature I need to find constants $c_1, c_2, x_1, x_2$

Skipping all the integration and getting right to the system I derived I have:

$$c_1 + c_2 = 2$$ $$c_1x_1 + c_2x_2 = 0$$ $$c_1x_1^2 + c_2x_2^2 = \frac{2}{3}$$ $$c_1x_1^3 + c_2x_2^3 = 0$$

I never learned how to solve such systems with quadratic and cubic members.

The book says "simple algebra" can be used to solve this, and the book provides the solutions

$$c_1 = 1, c_2 = 1, x_1 = \frac{-\sqrt{3}}{3}, x_2 = \frac{\sqrt{3}}{3}$$

How are these derived?

Thank you!


Assume that neither $x_1$ nor $x_2$ is zero (you can rule this out by simple testing).

Then the 2nd and 4th equations imply that $c_1x_1=-c_2x_2$ and $c_1x_1^3=-c_2x_2^3$, respectively. Then we can divide the corresponding sides of each of these equations to get that $$x_1^2=x_2^2$$ so the 3rd equation becomes $$(c_1+c_2)x_1^2=2/3$$ But then the first equation tells us that $$2x_1^2=2/3$$ so $$x_1=\pm\sqrt{3}/3$$ and thus also $$x_2=\pm\sqrt{3}/3.$$

Note that we can't have that $x_1=x_2$, since then the 2nd equation would imply that $c_1+c_2=0$. Therefore, $x_2=-x_1$, and the 2nd equation then implies that $c_1 = c_2$. The first equation then tells us that $$c_1=c_2=1.$$

So we have that $$\boxed{c_1=c_2=1}$$ and $$\boxed{x_1=\pm\sqrt{3}/3}$$ and $$\boxed{x_2=\mp\sqrt{3}/3}.$$

The $x_i$ can be interchanged, as long as they have opposite signs. You can see this in the original equations--swapping them doesn't change the equations.

  • $\begingroup$ Brilliant answer. Thank you. $\endgroup$ – John Dec 5 '14 at 4:36

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.